EFEKTIVITAS STRATEGI PERCEPATAN PENYELESAIAN STUDI PROGRAM S1 FAKULTAS TARBIYAH IAIIG CILACAP - Zulfa, Umi; Kurniasih, Nani (IAIIG Cilacap, 2017)
Effectiveness of Acceleration of Completion Strategy Study Program S1 Faculty Tarbiyah IAIIG Cilacap The purpose of this research is to: 1) know the policy, 2) to identify the various strategies, 3) to identify the variety of programs, and 4) to analyze the effectiveness level of the acceleration strategy of S1 studies at the IAIIG Cilacap Tarbiyah Faculty from 2013-2016. This research uses qualitative descriptive approach, with interview and documentation method. The findings of this research are: 1) Acceleration policy of S1 study in Faculty of Tarbiyah IAIIG Cilacap from 2013 to 2016 there are 5 policies, namely: a) Development of Curriculum 2010 and 2014 which mandate thesis loaded sks 6, b) Determination of Thesis Supervisor and Reviewer, Which then becomes mentor 1 and 2, c). Periodization Graduation twice in one academic year, d) Short Semester, conducted at faculty level since 2013 and 2014 established as institute policy and e) Setting the ideal Study Period for S1 as much as 8 semesters, 2) Some acceleration strategy of S1 study is : A) to synergize the courses of MPP, PPL and Thesis, b) to describe the distribution of subjects that support the completion of final project work in such a way done earlier, such as subjects of MPS, MPP, PTK, statistic and KKN, c) research worshop and e)